Implementation of non-insulin-dependent diabetes self-management education (DSME) in LMICs: a systematic review of cost, adoption, acceptability, and fidelity in resource-constrained settings - Fitzpatrick, Reilly; Pant, Shubhra; Li, Jamie; Ritterman, Rebecca; Adenikinju, Deborah; Iloegbu, Chukwuemeka; Pateña, John; Vieira, Dorice; Gyamfi, Joyce; Peprah, Emmanuel (Frontiers in Health Services, 2023)
Background: Type II diabetes (T2D), is a serious health issue accounting for 10.7% of mortality globally. 80% of cases worldwide are found in low- and middle-income countries (LMIC), with rapidly increasing prevalence. Diabetes-self management education (DSME) is a cost-effective program that provides at-risk individuals with the knowledge and skills they need to adopt lifestyle changes that will improve their health and well-being. This systematic review examined the application of DSME in LMICs and identified the corresponding implementation results (cost, fidelity, acceptance, and adoption) associated with successful implementation in low-resource settings. Methods and analysis: The available research on T2D and the use of DSME in LMIC were systematically searched for using six electronic databases (PubMed, Embase, Cochrane, Web of Science, Google Scholar, PAIS, and EBSCO Discovery) between the months of October and November of 2022. The articles that met the search criteria were subsequently imported into EndNote and Covidence for analysis. The Cochrane RoB methodology for randomized trials was used to evaluate the risk of bias (RoB) in the included studies. A narrative synthesis was used to summarize the results. Result: A total of 773 studies were imported for screening, after 203 duplicates were removed, 570 remained. Abstract and title screenings resulted in the exclusion of 487 articles, leaving 83 for full-text review. Following a full-text review, 76 articles were excluded and seven were found to be relevant to our search. The most common reasons for exclusion were study design (n=22), lack of results (n=14), and wrong patient population (n=12). Conclusion: Our systemic review found that DSME can be an acceptable and cost-effective solution in LMIC. While we intended to analyze cost, adoption, acceptability, and fidelity, our investigation revealed a gap in the literature on those areas, with most studies focusing on acceptability and cost and no studies identifying fidelity or adoption. To further evaluate the efficacy of DSME and enhance health outcomes for T2D in LMICs, more research is needed on its application.